Taxonomic studies on Dolichothrips (Thysanoptera: Phlaeothripinae), pollinators of Macaranga trees in Southeast Asia (Euphorbiaceae) - Mound, Laurence A.; Okajima, Shûji (Zootaxa, 2015)
Five new species associated with the inflorescences of Macaranga trees are described in the Asian genus Dolichothrips Karny. Four of these, chikakoae, eriae, fialae and utae, are from the Malaysian region where they are involved in the pollination of these trees. The fifth, franae, is described from the Hawaiian Islands but is probably introduced from Southeast Asia, and this species appears also to be a pollinator of its host plant. In contrast, little is known of the biology of the many species of Dolichothrips from India. However, D. indicus (Hood) is here interpreted as a variable, polyphagous and widespread species around the tropics, with D. nesius Stannard and D. pumilus Priesner placed as new synonyms. D. reuteri (Karny) from Australia, is also not restricted to Macaranga, and D. flavipes (Moulton) from Taiwan is here considered a new synonym of reuteri. An identification key is provided to 15 species of this genus, but this excludes five species for which specimens were not available. D. citricrurus Moulton, described from Ethiopia, is transferred to Apelaunothrips Karny.